Outer shelf claims in the South China Sea: new dimension to old disputes - Bateman, Sam (2016)
Submissions by Malaysia and Vietnam to the UN regarding continental shelf areas beyond 200 nautical miles from their mainland coasts in the South China Sea have provoked a furious response from China. What are the implications for the South China Sea disputes?